Gaya Kepemimpinan Path Goal Theory dan Produktivitas Pamong Desa - Siti Nur Azizah (Jurnal E-Bis (Ekonomi-Bisnis), 2021)
Aim of this research toexaminethe effect of path goal leadershipstylesonvillage officials productivity. Quantitative descriptive research methods are used to explain phenomena and analyze the influence of leadership style and productivity. 100 samples from village staff in Kebumen Distric, Central Java Indonesia filled out randomly selected questionnaires and the data were processed using SPSS 25. Hypothesis and correlation tests were carried out and the results showed is that achievement-oriented leadership styles of path-goal theory has a significant effect that can be used to increase the productivity of the village officials. Meanwhile, the directive leadership style, supportive leadership style and participative leadership style did not affect the productivity of the village officials. The results of this study concluded that an achievement-oriented leadership style can be applied as a leadership model to increase the productivity of the village officials